Estudo e seleção de um aparelho de ar condicionado para ônibus - Li, Fernando Liang [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The study and selection of an equipment of air conditioner for any type of environment, should be made without overestimate or undersizing the project. The undersizing does not provide an adequate comfort temperature if the environment is too hot because the air conditioner does not remove all the heat necessary in the environment. But if the project is oversized, energy consumption is higher and there is an unnecessary cost. To prevent these failures is necessary to make a calculation of the thermal load on the environment and choose the equipment that has a higher cooling capacity than the calculated heat load and closer to the calculated heat load. In this graduate work will be chosen an air-conditioned equipment for bus, showing the calculations made for the thermal load for various types of heat gain in this type of vehicle. The thermal load on vehicles is more complicated to calculate than in areas because there are several factors that vary with the movement of the vehicle. It will also explain the compression refrigeration cycle, which is the cooling system used in vehicles because it is weightless, compact and lower cost. From the calculated heat load, it will be chosen an air conditioner that best suits the project and, finally, a brief presentation of the selected equipment will be made

O estudo e a seleção de um aparelho de ar-condicionado, para qualquer tipo de ambiente, deve ser feita de modo a não subdimensionar ou superdimensionar o projeto. O subdimensionamento não proporciona uma temperatura de conforto adequada, uma vez que o ambiente ficará muito quente, pois o aparelho de ar-condicionado não retira todo o calor necessário. Porém se o projeto for superdimensionado, o consumo de energia para movimentar o sistema é maior, exigindo um gasto desnecessário. Para evitar que essas falhas ocorram é necessário, primeiramente, fazer um cálculo da carga térmica do ambiente e, assim, escolher o aparelho que tiver a capacidade de refrigeração superior e mais próxima da carga térmica calculada. Neste trabalho, será considerada a escolha de um aparelho de arcondicionado para ônibus, mostrando o cálculo realizado para a carga térmica para diversos tipos de ganho de calor neste tipo de veículo. A carga térmica em veículos é mais complicada de se calcular do que em recintos, devido a diversos fatores que variam conforme a locomoção do veículo. Será também explicado o ciclo de refrigeração por compressão, que é o sistema de refrigeração normalmente empregado em veículos por ser leve, compacto e menor custo. A partir da carga térmica calculada, será escolhido um aparelho de ar-condicionado que melhor atende o projeto e, finalmente, uma breve apresentação sobre o aparelho escolhido será feita
Keywords: Ar condicionado; Carga termica; Efeito estufa (Atmosfera); Air-conditioner; Thermal load